2019
DOI: 10.1101/530592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using environmental DNA for the detection of Schistosoma mansoni: toward improved environmental surveillance of schistosomiasis

Abstract: Schistosomiasis is a waterborne, infectious disease with high morbidity and significant economic burdens affecting more than 250 million people globally. Disease control has, with notable success, for decades focused on drug treatment of infected human populations, but a recent paradigm shift now entails moving from control to elimination. To achieve this ambitious goal more sensitive diagnostic tools are needed to monitor progress towards transmission interruption in the environment, especially in low-intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…from these organisms. Previous studies with invertebrates and parasites in mesocosms have reported more variable detection success, in accordance with our findings (but see Sengupta et al 2019 for 100 % detection efficiency of Schistosoma mansoni). Mauvisseau et al (2019) sampled water from mesocosms containing Freshwater Pearl Mussels (Margaritifera margaritifera) and were able to detect their DNA in all mesocosms with only one of two assays used, with evidence for inconsistent detection in biological and technical replicates.…”
Section: Parasite Detection and Occupancysupporting
confidence: 93%
See 1 more Smart Citation
“…from these organisms. Previous studies with invertebrates and parasites in mesocosms have reported more variable detection success, in accordance with our findings (but see Sengupta et al 2019 for 100 % detection efficiency of Schistosoma mansoni). Mauvisseau et al (2019) sampled water from mesocosms containing Freshwater Pearl Mussels (Margaritifera margaritifera) and were able to detect their DNA in all mesocosms with only one of two assays used, with evidence for inconsistent detection in biological and technical replicates.…”
Section: Parasite Detection and Occupancysupporting
confidence: 93%
“…Knowledge of pathogens in the environment is also important for human health and for the mitigation and prevention of zoonoses (Cunningham et al 2017). Furthermore, it eases planning of disease control, and even informs eradication measures, for example of Schistosoma mansoni in Kenya (Sengupta et al 2019). Therefore, comprehensive and regularly updated monitoring campaigns and surveillance for the creation of maps of parasite prevalence (Diarra et al 2019) are important to implement management measures effectively.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the problem of compensatory feedbacks, the observation of density feedbacks warrants the evaluation of the effect of reductions in snail populations in terms of transmission potential to humans as subject to non-linearities in cercarial productivity with resource availability [35,36]. Novel approaches leveraging DNA-based tools such as PCR for the identification of snail and schistosome species [3], as well as environmental-DNA (eDNA) quantification techniques recently developed for schistosomes can play in important role in investigating these issues [64].…”
Section: Discussionmentioning
confidence: 99%
“…Biological invasions, pests, and diseases constitute one of the most serious threats for global biodiversity and cause adverse environmental, economic and public health impacts (Sengupta et al 2019;Tingley et al 2019;Walsh et al 2019). There is thus an urgent need to develop effective monitoring and management strategies to contain the spread and establishment of these harmful biological agents (Marshall & Stepien 2019;Orzechowski et al 2019).…”
Section: Biomonitoring Ecosystem Health and Dynamicsmentioning
confidence: 99%